2021
DOI: 10.3390/agronomy11091755
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Biostimulant to Mitigate Salt Stress in Maize Plants

Abstract: Salinity is considered among the abiotic stresses most impacting agriculture for its ability to interfere with crop development and quality. For this reason, practices and innovations that could contain the deleterious effects of such stress are of pivotal importance for maintaining acceptable crop yields. In this context, this work has concerned the study of severe salt stress (100 mM NaCl) on maize seedlings and the effects of a plant biostimulant (Megafol–Meg) in helping plants to cope with this adversity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
(89 reference statements)
1
9
0
Order By: Relevance
“…Li et al ( 35 ) reported that a novel PGPR strain, Kocuria rhizophila , mitigated the deleterious effects of salinity on maize growth and development by regulating plant hormones and nutrient acquisition, thereby maintaining ionic homeostasis and improving photosynthesis. A plant biostimulant (Megafol-Meg) was also found to reduce the impacts of salt stress on maize growth and photosynthetic pigments by reducing the contents of H 2 O 2 , MDA, and total phenolic compounds (TPC) after inoculation ( 2 ). Therefore, the changes in physiologies caused by inoculants are one of the reasons for the improved growth of maize under salt stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al ( 35 ) reported that a novel PGPR strain, Kocuria rhizophila , mitigated the deleterious effects of salinity on maize growth and development by regulating plant hormones and nutrient acquisition, thereby maintaining ionic homeostasis and improving photosynthesis. A plant biostimulant (Megafol-Meg) was also found to reduce the impacts of salt stress on maize growth and photosynthetic pigments by reducing the contents of H 2 O 2 , MDA, and total phenolic compounds (TPC) after inoculation ( 2 ). Therefore, the changes in physiologies caused by inoculants are one of the reasons for the improved growth of maize under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, one of the most serious problems associated with soil is salinization, which has a substantial impact on crop growth and development. It has been estimated that more than 800 million hectares arable in the world are affected by soil salinization and that the area of salinized land will continue to rise in the future ( 1 , 2 ). Salt stress can reduce crop yields by up to 50% or more, resulting in negative ecological and socioeconomic consequences ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Salinity is considered among the abiotic stresses most impacting agriculture for its ability to interfere with crop development and quality. For this reason, practices and innovations that could contain the deleterious effects of such stress are of pivotal importance for maintaining acceptable crop yields [44]. In the last few years, research has shown that the use of salt-tolerant plant growth promoting rhizobacteria (ST-PGPR) in saline agriculture can be harnessed for enhancing productivity and improving soil fertility as well [45].…”
Section: Discussionmentioning
confidence: 99%
“…This strain stored at −85 • C in Mueller Hinton nutrient broth with addition of glycerol (10%) in the laboratory was isolated and identified by [28] and characterized by [7] for its PGPR profile. The ability of P. putida to grow under different temperatures (4,16,25,30,37,40,44,48, and 50 • C) was performed by the method adapted by [29] on Mueller Hinton (MH) liquid nutrient broth inoculated with 100 µL of the bacterial culture of the tested strain for 48 h under agitation. The growth of P. putida was evaluated by reading the optical density (OD) with a spectrophotometer (BioMATE 3S, Thermo scientific, Waltham, MA, USA) at the wavelength of 600 nm and the experiments were performed in three r replicates.…”
Section: Methodsmentioning
confidence: 99%
“…One of the promising and novel applications to deal with abiotic stress conditions including salinity stress is the use of biostimulants in agricultural production [ 10 ]. Biostimulants, which contain a wide variety of bioactive compounds, have positive effects on plant metabolism such as in increasing the nutrient utilization efficiency and improving crop tolerance to biotic and abiotic stresses; although, their modes of action are not fully understood [ 11 ].…”
Section: Introductionmentioning
confidence: 99%